KOMUNIKASI DALAM PERSPEKTIF IMPERIALISME KEBUDAYAAN - Heldi Yunan Ardian (Universitas Muhammadiyah Jakarta, 2018)
Globalization has removed the boundaries of communication systems between one region and another region that is transferred very fast through various media such as television, magazines, and internet. National culture in a country is rapidly becoming a global culture and becoming a capable industry in influencing national culture in other countries. Cultural In the era of reform, imperialism appears to be more prominent than the previous regime era that influenced all the joints of economic, political and cultural life. Cultural imperialism today, not only from the West but also from non-Westerners like India, Korea, China, Japan and Turkey. In response to this, an open cultural strategy is needed to take the universal values in all areas of science, technology, economics and culture without losing the identity as a sovereign and dignified nation in the midst of other nations. Traditional culture is a valuable national treasure and does not bother the process of development and modernization.Keywords: globalization, imperialism, identity